More Problems, More Pain: The Role of Chronic Life Stressors and Racial/Ethnic Identity on Chronic Pain Among Middle-Aged and Older Adults in the United States - Antoinette L. Spector; Katherine G. Quinn; Inga Wang; Jordan A. Gliedt; Roger B. Fillingim; Yenisel Cruz-Almeida (Chronic Stress, 2023)
There is a high prevalence of chronic pain among middle-aged and older adults in the United States. Chronic life stressors have been shown to have detrimental consequences for myriad health conditions, including chronic pain. However, there is limited evidence on the types of chronic life stressors that affect middle-aged and older adults and how these stressors influence the chronic pain burden in this population. Moreover, the interaction between chronic life stressors and racial/ethnic identity remains poorly understood as it relates to chronic pain. The current analysis used the 2018 Health and Retirement Study to investigate relationships between chronic life stressors and odds to experience any chronic pain and high-impact chronic pain. Chronic life stressors were characterized, overall and by racial/ethnic identity, and the main and interaction effects were calculated to evaluate relationships between chronic life stressors, racial/ethnic identity, and odds of experiencing any chronic pain and high-impact chronic pain. Results indicate that in 2018, the most common chronic life stressor among middle-aged and older adults was dealing with their own health problems (68%), followed by dealing with the physical or emotional issues affecting a spouse or child (46%). Adjusted analyses showed that a higher total of chronic life stressors increased the odds of middle-aged and older adults experiencing any chronic pain and high-impact chronic pain. There were no significant interactions between the overall chronic life stress burden and racial/ethnic identity as a predictor of odds to experience any chronic pain or high-impact chronic pain, but significant interaction effects were found related to specific chronic life stressors. Findings underscore the significant impact of chronic life stressors on the chronic pain burden among middle-aged and older adults in the United States, which cut across racial/ethnic identity.